Dynamics of pulmonary hypertension severity in the first 48 h in neonates with prenatally diagnosed congenital diaphragmatic hernia - Leyens, Judith; Schroeder, Lukas; Geipel, Annegret; Berg, Christoph; Bo, Bartolomeo; Lemloh, Lotte; Patel, Neil; Mueller, Andreas; Kipfmueller, Florian (Frontiers in Pediatrics, 2023)
Introduction Pulmonary hypertension (PH) is one of the major contributing factors to the high morbidity and mortality in neonates with congenital diaphragmatic hernia (CDH). The severity and duration of postnatal PH are an established risk factor for patient outcome; however, the early postnatal dynamics of PH have not been investigated. This study aims to describe the early course of PH in CDH infants, and its relation to established prognostic markers and outcome measures. Methods We performed a monocentric retrospective review of neonates with prenatally diagnosed CDH, who received three standardized echocardiographic examinations at 2-6 hours, 24, and 48 hours of life. The degree of PH was graded as one of three categories: mild/no, moderate, or severe PH. The characteristics of the three groups and their course of PH over 48 hours were compared using univariate and correlational analyses. Results Of 165 eligible cases, initial PH classification was mild/no in 28%, moderate in 35%, and severe PH in 37%. The course of PH varied markedly based on the initial staging. No patient with initial no/mild PH developed severe PH, required extracorporeal membrane oxygenation (ECMO)-therapy, or died. Of cases with initial severe PH, 63% had persistent PH at 48 hours, 69% required ECMO, and 54% died. Risk factors for any PH included younger gestational age, intrathoracic liver herniation, prenatal fetoscopic endoluminal tracheal occlusion (FETO)-intervention, lower lung to head ratio (LHR), and total fetal lung volume (TFLV). Patients with moderate and severe PH showed no difference in these characteristics, except in their mortality (p=0.001) and ECMO-rate (p=0.035). Discussion To our knowledge, this is the first study to systematically assess the dynamics of PH in the first postnatal 48 hours at three defined time points. CDH infants with initial moderate and severe PH have a high variation in postnatal PH severity over the first 48 hours of life. Patients with mild/no PH have less change in PH severity, and an excellent prognosis. Patients with severe PH at any point have a significantly higher risk for ECMO and mortality. Assessing PH within 2-6 hours should be a primary goal in the care for CDH neonates.